Susceptibility Analysis of Printed Circuit Boards Within Cavity Enclosures - Yang, Taesik; Volakis, John L. (Electromagnetics, 2011)
This article considers the susceptibility of enclosed printed circuit board structures subject to external electromagnetic fields using a simple and efficient analysis. The method employs the magnetic currents on the nonmetallic surface of the cavity enclosing the multi-layer printed circuit boards. By using magnetic currents, coupling from one layer of the cavity to the other is conducted. In this manner, a single cavity Green's function is needed, avoiding the time-consuming modeling of junctions and vertical interconnects associated with multi-layer Green's functions. To validate the proposed method, numerical results and parametric studies are presented.